A Question of Sacrifice: The Deep Structure of Deaths in Police Custody. (June 2020) - Loader, Ian
Deaths in police custody present a set of enduring and troubling puzzles. Why do such deaths seldom result in prosecutions or adequate redress? Why are victims' families so under-resourced and typically met with a conflicted mix of empathy and hostility? Why do acknowledged problems remain unresolved despite review after review making the same criticisms and seemingly consensual recommendations? Why is the state's failure to fulfil its duty of care towards those it detains met with public indifference? In this article, I argue that we can shed new light on these questions if we theorize and investigate police power using the metaphor of sacrifice. Thinking about police power through this lens enables us to identify and illuminate a conflict between the liberal rationality that appears to govern responses to custodial deaths and the illiberal values and affects that constitute what I term the deep structure of deaths in police custody. By re-examining reports of recent enquiries into the issue, I outline four recurring elements of this deep structure and show how they clash with surface liberal rationalities. The systemic reduction of custodial death requires, I conclude, that we name and contest the quasi-sacred conception of police authority that holds the police vital to the production of order and control and its agents to require protection when things 'go wrong'.